Techno-Economic Optimization and Unification of 10 kV Urban Distribution Network Parameters Using Criteria-Based Modeling - Taslimov Abdurakhim Dekhkanovich; Melikuziev Mirkomil Vokhidjon Ugli; Ponniran, Asmarashid; Samiev Shokhruh Salim Ugli; Muminov Vakhob Usan Ugli; Aminov Khamza Murod Ugli; Turaev A’zam Ikromjonovich (International Journal of Integrated Engineering, 2026)
The optimization and unification of cable cross-sections in urban distribution electrical networks (DENs) is an important techno-economic problem, particularly for 10 kV medium-voltage (MV) networks where construction, installation, and operational costs are significant. This study aims to develop an integrated criteria-based techno-economic optimization model for determining economically justified network parameters while considering cable cross-section unification. The proposed model jointly optimizes the number of outgoing feeders, feeder cable cross-sections, and the number of standardized cable cross-sections within a 10 kV urban distribution network supplied from a common power source (PS). The model is based on topological representations of urban distribution network sections and incorporates capital expenditures, installation costs, operating costs, and electric energy losses. The optimization is performed using criteria-based programming, which allows analytical expressions to be obtained without numerous variant-based calculations. The results show that cable cross-section unification is economically justified when it is optimized together with other network parameters. For urban areas with load density σ≥10 MVA/km², the use of one or two standardized cable cross-sections is optimal, whereas for lower load densities σ